Analysis of The Teaching Quality of English MGMP Members in Topoyo Subdistrict - Prawito Prawito; Zulfah Zulfah; Magdahalena Tjalla; Mujahidah Mujahidah; Saepudin Saepudin (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Theoretically, teachers' role in MGMP activities enhances English teaching quality and comprehension. This study aims to identify the activities conducted within the Teacher Working Group (MGMP) in Topoyo Subdistrict, Central Mamuju District, that can enhance the English teaching capabilities of senior high school teachers. The primary focus of this research is to describe the teaching quality of MGMP teachers in the area during the 2023/2024 academic year. Through collaboration in lesson planning, peer observation, and reflective discussions, this study seeks to explore the positive impact of MGMP on the development of English teachers' teaching quality. This research employs a qualitative descriptive approach with a phenomenological method to explore the MGMP activities that influence English teaching quality. The subjects consist of 6 English teachers from 6 different schools in Topoyo Subdistrict, with ages ranging from 30 to 50. The instruments used include structured interviews, direct observation, and documentation of MGMP activities. Interviews were conducted with audio recordings, while observations aimed to confirm data obtained from interviews. The collected data were analyzed through stages of data reduction, data display, and conclusion drawing and verification to ensure the validity of the findings. The results of this study indicate that; 1) The MGMP activities in Topoyo Sub-district enhance English teachers' competencies through collaboration, peer observation, and reflection. Using the innovative strategies such as project-based learning and differentiated instruction are applied to align with the student-centered Merdeka Curriculum. This approach helps teachers address challenges like varying student abilities and limited resources, while promoting adaptive, collaborative teaching practices that support the development of higher-order thinking skills. 2) The MGMP English teachers in Topoyo showed their ability to integrate contemporary pedagogical theories and strategies such as active, contextual, and student-centered learning while adapting to classroom challenges. These practices contributed to a teaching quality that is reflective, adaptive, collaborative, and responsive to the demands of 21st-century education and the diverse needs of students. To further improve teaching quality, it is recommended that teachers provide diverse learning opportunities and ensure equal access to technology for all students.